Project for Offshore Horizontal Directional Drilling (HDD) for Pipeline Crossing in Bukit Tua, Indonesia - Yusuf Sofyan (Universitas Pendidikan Indonesia, 2016)
Horizontal Directional Drilling (HDD) is commonly associated with well exploration activity, onshore road crossing, nearshore pipeline installation, and offshore pipeline crossing which requires precise alignment of two barges from one to the other. Here, the purpose of this study was to show one of the projects that was successfully performed on December 2013 for the Bukit Tua Project in East Java, Indonesia costing USD 8 Million. From this project experience, there are 6 Best Practices in HDD Offshore Project for Pipeline Crossing Application (first in region) which will serve as a guide to future projects in replicating similar success. Out from 6 Best practices, there are two main recipes for success of HDD offshore for offshore crossings which are the drilling fluid also known as mud, and the Gyro Steering Tool (GST). First, mud parameter varies on case by case basis depending on the soil condition at the location where HDD will be performed. Failure to maintain the above parameters may result in catastrophic failure whereby the bore hole may collapse and pipe may get stuck underneath the seabed. Secondly, the beauty of GST is extremely accurate and unaffected by other metal anomalies during drilling process, thus ensuring the curve profile and direction of drilling are as per design throughout the whole process.